2021
DOI: 10.1371/journal.pone.0259602
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial uropathogens and burden of antimicrobial resistance pattern in urine specimens referred to Ethiopian Public Health Institute

Abstract: Background Urinary tract infections (UTIs) are the leading causes of morbidity in the general population, and is the second most common infectious disease after respiratory infections. Appropriate antibiotic therapy is essential to achieving good therapeutic results. Therefore, the purpose of this study was to investigate the profile of pathogens cultured from urinary tract infections and to determine their resistance profiles to commonly prescribed antibiotics. Method A cross-sectional study was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
1
12
2
Order By: Relevance
“…Among the Gram-positive bacteria, 58.8% of isolates were MDR, which is comparable to a study done in Gondar [ 21 ]. In this study, the overall percentage of XDR isolates was 15.8, which is comparatively lower than that reported in an earlier study in the country [ 18 ]. Results of the present study indicated that 57.1% (12/21) of Gram-negative bacilli were ESBL-positive.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Among the Gram-positive bacteria, 58.8% of isolates were MDR, which is comparable to a study done in Gondar [ 21 ]. In this study, the overall percentage of XDR isolates was 15.8, which is comparatively lower than that reported in an earlier study in the country [ 18 ]. Results of the present study indicated that 57.1% (12/21) of Gram-negative bacilli were ESBL-positive.…”
Section: Discussioncontrasting
confidence: 83%
“…Several emerging bacterial pathogens are extremely resistant to existing treatment regimens due to their physiology or growth characteristics, and uropathogens are of no exception [ 17 , 18 ]. Recently, bacterial uropathogens in the paediatric patient group became highly resistant to commonly used antibiotics such as ampicillin, co-trimoxazole, fluoroquinolones and the third generation cephalosporins, and these drugs became unsuitable for empirical use [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a 17.39% prevalence of P. aeruginosa was reported among uropathogenic bacteria which is significantly higher than the 4% reported by Brown et al in asymptomatic UTIs in Wukari [22]. Similar studies have also reported lower prevalence rates of Pseudomonas aeruginosa in UTIs than that reported in this study [1,[23][24][25][26][27][28][29][30][31]. However, the reported prevalence is lower than the 18.70% reported in Egypt [32].…”
Section: Discussioncontrasting
confidence: 48%
“…Analogous results have revealed from earlier published studies: Addis Ababa (22.6%), 18 Gondar (17.8%), 15 Metu (16.7%), 14 Nekemete (16.5%), 34 Sudan (19.5%), 19 and Uganda (22.0%). 35 However, this finding was relatively lower as compared to the studies conducted in Arba Minch, Ethiopia (33.8%), 12 in Addis Ababa (32.1%), 36 Nigeria (40%), 37 Nepal (54.76%), 38 and Pakistan (49.2%). 39 On the contrary, our finding is higher than other studies conducted in Addis Ababa (10.9%) 21 and Dessie (11.6%).…”
Section: Discussionmentioning
confidence: 68%